Impedance Model Study of Duct Sound Liner under High Speed Airflow - YAN Meng; FU Liang; ZHA Guotao; HE Caichun (Kongzhi Yu Xinxi Jishu)
Micro perforation plate (MPP) sound liner is a very effective method to control pipe noise in high-speed airflow environment based on the principle of Helmholtz resonator. It generally has single layer, double-layer or even multi-layer structure. At present, the acoustic design theory of MPP sound liner is mature and reliable in the absence of air flow, but the design process is complicated in the presence of air flow, especially in the environment of high-speed air flow, and there are many influencing factors, so it has not formed a mature and unified theoretical basis for design. In this paper, an acoustic impedance model of double-layer MPP sound liner with two resonant frequencies is derived which is based on the acoustic impedance model of single layer MPP sound liner by the transfer matrix method (TMM). The model is used to calculate acoustic impedance and acoustic absorption of a known double-layer MPP sound liner at 130 dB sound intensity level and 60 m/s velocity. At the same time, the flow tube method is used for measurement. The results show that the theoretical results are close to the measured results. The maximum error of sound absorption coefficient is only 0.05, which can meet the requirements of engineering application.